Association between polymorphisms of genes involved in the Renin‑Angiotensin‑Aldosterone System and the adaptive morphological and functional responses to essential hypertension. Issue 4 (13th July 2021) - MOCAN, OANA; RĂDULESCU, DAN; BUZDUGAN, ELENA; LEUCUTA, ANGELA COZMA DANIEL CORNELIU; BOGDAN, SIDONIA ALINA; PROCOPCIUC, LUCIA MARIA
No abstract available